1999
DOI: 10.1038/sj.bjp.0702581
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of impaired K+ channels in mesenteric arteries from spontaneously hypertensive rats by prolonged treatment with cholecalciferol

Abstract: 1 The mechanism responsible for blood pressure reduction in spontaneously hypertensive rats (SHR) after prolonged cholecalciferol treatment was studied. Two-week treatment of SHR with 0.125 mg cholecalciferol kg 71 body weight per day orally caused signi®cant reductions of systolic blood pressure and of the resting perfusion pressure of the mesenteric vascular bed at constant¯ow. 2 In addition, the treated animals presented a normalization of the maximum vasoconstriction response to noradrenaline and a reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
2
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 26 publications
(38 reference statements)
6
44
2
1
Order By: Relevance
“…The hyperpolarization induced by this agonist was lower in the SHR than in the NWR vessels, indicating that NO release was deficient in the hypertensive animals. This agrees with previous findings in SHR mesenteric arteries 14 and in cultured endothelial cells, which show NO deficiency in SHR 21 caused by increased destruction by super oxide. 22,23 We followed the changes of carotid smooth muscle membrane potential as well as endothelin plasma concentration for several days after angioplasty (Figures 3 and 4).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The hyperpolarization induced by this agonist was lower in the SHR than in the NWR vessels, indicating that NO release was deficient in the hypertensive animals. This agrees with previous findings in SHR mesenteric arteries 14 and in cultured endothelial cells, which show NO deficiency in SHR 21 caused by increased destruction by super oxide. 22,23 We followed the changes of carotid smooth muscle membrane potential as well as endothelin plasma concentration for several days after angioplasty (Figures 3 and 4).…”
Section: Discussionsupporting
confidence: 83%
“…In previous articles, 13,14 we reported that SHR mesenteric artery smooth muscles are less polarized than those of normotensive Wistar rats (NWR). This was attributed to different alterations, such as impairment of the activity of K ϩ channels coupled to ␣ 2 -adrenoceptors or diminished NO production in the SHR.…”
mentioning
confidence: 99%
“…3 Studies in spontaneously hypertensive rats have shown decreased blood pressure on oral administration of supplemental vitamin D, as well as improvements in endothelial cell-dependent vasodilation. [5][6][7] Two cross-sectional studies examining vitamin D intake and blood pressure in humans reported conflicting results. Sowers et al examined 86 normotensive young women (20 to 35 years of age) and 222 normotensive older women (55 to 80 years of age).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Oral supplementation with vitamin D lowers blood pressure in hypertensive rats. [5][6][7] In humans, cross-sectional data suggest an association between low vitamin D intake (Ͻ400 IU per day) and higher blood pressure, 8 and a single interventional study in vitamin D-deficient elderly women found that a combination of calcium and vitamin D supplementation had a greater blood pressure-lowering effect than calcium supplementation alone. 9 However, there are no prospective data in the general population that higher vitamin D intake lowers the risk of hypertension.…”
mentioning
confidence: 99%
“…In SHR, an impaired K v activity was found in the aorta (Cox, 1996) and an impaired K Ca and K ATP activity was found in the MA (Ohya et al, 1996;Borges et al, 1999). Since ROS have emerged as a significant determinant of K þ channel activity (Liu & Gutterman, 2002) and production of ROS is higher in hypertension, we hypothesized that the vascular relaxation response to H 2 O 2 is altered in SHR MA, and that this alteration is related to changes in K þ channel activity.…”
Section: Introductionmentioning
confidence: 99%